2012
DOI: 10.1128/iai.00442-12
|View full text |Cite
|
Sign up to set email alerts
|

Abscess Formation and Alpha-Hemolysin Induced Toxicity in a Mouse Model of Staphylococcus aureus Peritoneal Infection

Abstract: ABSTRACTStaphylococcus aureusis a frequent cause of skin infection and sepsis in humans. Preclinical vaccine studies withS. aureushave used a mouse model with intraperitoneal challenge and survival determination as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 51 publications
3
79
0
Order By: Relevance
“…Indeed, it has been demonstrated to be essential for disease in several animal models of infection (5)(6)(7)(8)(9)(10)(11). Considering its importance, it is not surprising that this toxin is under tight regulatory control to ensure that its production is adapted to the varied microenvironments and immune modulators present within the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated to be essential for disease in several animal models of infection (5)(6)(7)(8)(9)(10)(11). Considering its importance, it is not surprising that this toxin is under tight regulatory control to ensure that its production is adapted to the varied microenvironments and immune modulators present within the host.…”
Section: Discussionmentioning
confidence: 99%
“…VfrB impacts virulence in an SSTI model. Alpha-hemolysin has been shown previously to be important in a variety of infection models (5)(6)(7)(8)(9)(10)(11)(12), and proteases are thought to contribute to pathogenesis by modulating secreted virulence factors and degrading host proteins (21,(28)(29)(30)(31)(32)(33)(34). To assess the contribution of VfrBregulated virulence factors in vivo, we chose a mouse model of dermonecrosis due to the following considerations: (i) S. aureus is the dominant cause of all skin and soft tissue infections (SSTI) in patients presenting to emergency departments in the United States (49); (ii) more than 90% of all S. aureus infections are SSTI (50, 51); (iii) our wild-type strain is derived from an SSTI isolate (39,52); and (iv) both alpha-hemolysin (8) and proteases have been demonstrated to contribute to skin infections (21).…”
Section: Figmentioning
confidence: 99%
“…This study utilized MRSA strain Xen 30 (Xenogen/Caliper Life Sciences, Inc.), which was derived from S. aureus strain 16 and contains a luxABCDE operon in the chromosome, allowing for detection via bioluminescence in vivo (30). Although MRSA strains can vary in alphatoxin production (31)(32)(33), the virulence of the study strain was confirmed as equivalent to that of USA300 in the model as used in our prior studies (25). The virulence of strain Xen 30 was assessed in a previous study and demonstrated to be equivalent to that of other clinically relevant MRSA strains in the SSSI murine model (25).…”
Section: Methodsmentioning
confidence: 99%
“…Using NRS384 as the template, DNA flanking the codon for histidine 35 of Hla was amplified by PCR. The two resulting PCR products were digested with BsaI and cloned (37) into pRP1276 that had been digested with BamHI and SalI, generating pRP1308, which carries the H35L mutation in the Hla sequence, previously shown to reduce hemolytic activity and virulence (38)(39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%